PENGARUH PEMBERIAN EKSTRAK AIR HERBA Bidens pilosa L. PADA RESPON IMUN SELULER MENCIT TERHADAP INFEKSI Listeria monocytogenes - , IKA YANTI MARFUATUSH SHOLIKHAH, S.SI. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Immune system could be specifically manipulated by vaccination or non specifically by the use of immunomodulator. Flavonoid have been reported to have some biological effects, one of them is immunomodulating effect. Bidens pilosa L. contains flavonoid which has not been clarified yet whether it has effect on cellular immune response. Objectives: To evaluate the effect of water extract of B. pilosa L. on cellular immune response in mice infected with Listeria monocytogenes Method: Seventy two female Balb/c mice were divided into six groups, consist of 12 mice. The first and second group received aquadest only (negative control). The third, fourth, and fifth group received B. pilosa L. water extract with different dose, i.e. 125 mg/kgBW/day, 250 mg/kgBW/day, dan 500 mg/kgBW/day, respectively. The sixth group received Panax ginseng extract 26 mg/kgBW/day as a positive control. The test material were given everyday for 14 days. On 15 th day, all groups except first group were infected with L. monocytogenes. On 0, 2, 4, and 7 after bacterial infection, 3 mice of each group were killed and then peritoneal macrophage and spleen lymphocyte were cultured. Phagocytosis activity was measured by the ability of mice peritoneal macrophages to phagocyte latex particles in vitro and lymphocyte proliferation activity was determined using MTT assay method. Results: B. pilosa L. water extract could increase cellular immune response in mice against L. monocytogenes infection, i.e. macrophage phagocytosis and spleen lymphocyte proliferation. There were a significant different between negative control group and group treated with 500 mg/kgBW/day of B. pilosa L. water extract. Conclusions: The water extract of Bidens pilosa L. enhanced the activity of macrophage phagocytosis and lymphocyte proliferation.